EFEK EKSTRAK JAHE PUTIH KECIL 70% TERHADAP NILAI KEKERASAN BASIS RESIN AKRILIK - Aserina Julianti Dwimartha; Debby Saputera; Titis Fitri Wijayanti (Universitas Lambung Mangkurat, 2018)
ABSTRACT Background : The hardness of denture base can be affected by the way a patient cleans the denture, one of them is the selection of denture cleansers. The alternative using natural ingredients currently developed in order to minimize side effects arising from synthetic materials. Small ginger is one of the medicinal plants also known have antifungal activity that can be used as denture cleanser. Purpose: The research purpose is to know the change of hardness acrylic resin after being immersed in 70% small ginger for 1 day 21 hours and 40 minutes. Method: This research is pure experimental research by pre-test and post-test with control group design using 21 specimens cylindrical heat cured acrylic resin with 30 mm diameters and 5 mm thickness which divided into three groups: 70% small ginger extract (experimental), alkaline peroxide (positive control) and akuades (negative control). Result: The hardness was measured before and after immersion using Vicker Hardness Tester. The average value of heat cured acrylic hardness change after immersion in the small ginger extract 70%, alkaline peroxide and aquades were (0,24), (0,24) and (0,15), respectively. Data were statistically analyzed by parametric test One Way ANOVA and Pos HOC LSD Test. Conclusion: There was no difference of hardness change between small ginger extract 70% with alkaline peroxide solution as denture cleanser, but there was difference of hardness change between small ginger extract 70% with aquades for 1 day 21 hours 40 minutes. ABSTRAK Latar Belakang: Kekerasan basis gigi tiruan dapat dipengaruhi cara pasien membersihkan gigi tiruan salah satunya pemilihan pembersih gigi tiruan. Alternatif saat ini dikembangkan bahan alami untuk meminimalisir efek samping yang ditimbulkan dari bahan sintetik. Jahe putih kecil adalah tanaman obat yang memiliki aktivitas antifungal yang dapat digunakan sebagai pembersih gigi tiruan. Tujuan: Tujuan penelitian ini untuk mengetahui perubahan kekerasan resin akrilik setelah direndam dalam jahe putih kecil 70% selama 1 hari 21 jam 40 menit. Metode dan bahan: Penelitian ini merupakan penelitian eksperimental murni dengan pretest and posttest with control group design, menggunakan 21 spesimen resin akrilik heat cured berbentuk silinder diameter 30 mm dan tebal 5 mm yang dibagi ke dalam 3 kelompok: ekstrak jahe putih kecil 70% (perlakuan), alkaline peroxide (kontrol positif) dan akuades (kontrol negatif). Hasil penelitian: Uji kekerasan dilakukan menggunakan Vicker Hardness Tester. Rerata nilai perubahan kekerasan resin akrilik tipe heat cured setelah direndam dalam kelompok ekstrak jahe putih kecil 70%, alkaline peroxide dan akuades berturut-turut sebesar (0,24) (0,24) dan (0,15). Data dianalisis secara statistik menggunakan uji parametrik One Way ANOVA dan uji Post Hoc LSD. Kesimpulan: Hasil penelitian tidak terdapat perbedaan kekerasan antara ekstrak jahe putih kecil 70% dengan larutan alkaline peroxide sebagai denture cleanser setelah dilakukan perendaman selama 1 hari 21 jam 40 menit.